SF5-Pyridylaryl-λ3-iodonium salts and their utility as electrophilic reagents to access SF5-pyridine derivatives in the late-stage of synthesis. Issue 27 (20th March 2017) - Das, Prajwalita; Takada, Masahiro; Matsuzaki, Kohei; Saito, Norimichi; Shibata, Norio
Abstract : Electrophilic SF5 -pyridylation of C, N, O and S-nucleophiles using diaryliodonium reagents is disclosed. Abstract : Electrophilic pentafluorosulfanyl (SF5 ) heteroarylation of target molecules using novel reagents is described. Unsymmetrical diaryliodonium reagents1 having 2-SF5 -pyridine have been synthesized in good yields. They are efficient electrophilic reagents for carbon and heterocentered nucleophiles, producing the corresponding SF5 -pyridine derivatives in good to excellent yields.